Effects of sn and zn seed layers on the electrical characteristics of Pd/ZnO thin-film schottky diodes grown on n-Si substrates - Somvanshi D.; Jit S. (My University, 2025)
The effects of Sn and Zn seed layers on the rectifying characteristics of Pd/ZnO thin-film Schottky diodes fabricated on n-Si substrates by the thermal evaporation method have been investigated in this letter. The field emission scanning electron microscopy images show the changes in the surface morphology of the ZnO thin film from nanocrystalline to nanoparticle, and nanocrystalline to nanowires structures when the substrates for film deposition are changed from the bare n-Si to Sn seed layer-coated n-Si and from bare n-Si to Zn seed layer-coated n-Si substrates, respectively. Furthermore, a dramatic enhancement in the rectification ratio of Pd/ZnO Schottky diodes is observed from a nominal value of (1.13×102) at ±2 V (for the device grown on the bare n-Si substrates) to a large value of (8.8510×2) for the device grown on Sn seed layer coated n-Si substrates and to a value of (7.564×10 3) for the Zn seed layer coated device. The effects of the seed layers on the series resistance, ideality factor, and barrier height of the Pd/ZnO thin-film Schottky devices are also investigated for the first time in this letter. © 2014 IEEE.